2012
DOI: 10.1371/journal.pone.0033250
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia Reduces Arylsulfatase B Activity and Silencing Arylsulfatase B Replicates and Mediates the Effects of Hypoxia

Abstract: This report presents evidence of 1) a role for arylsulfatase B (ARSB; N-acetylgalactosamine-4-sulfatase) in mediating intracellular oxygen signaling; 2) replication between the effects of ARSB silencing and hypoxia on sulfated glycosaminoglycan content, cellular redox status, and expression of hypoxia-associated genes; and 3) a mechanism whereby changes in chondroitin-4-sulfation that follow either hypoxia or ARSB silencing can induce transcriptional changes through galectin-3. ARSB removes 4-sulfate groups fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
105
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 47 publications
(116 citation statements)
references
References 51 publications
(70 reference statements)
11
105
0
Order By: Relevance
“…This finding is consistent with the reported decline in binding of galectin-3, -7, and -9 to more highly sulfated chondroitin, which was observed by frontal affinity chromatography (23). Coincident with reduced binding of galectin-3 to C4S, we have shown increases in nuclear galectin-3, which enabled transcriptional events mediated by AP-1, including increased expression of HIF-1␣ and versican, in human bronchial, colonic, and prostate cells (21,22). Galectin-3 interacts with heterogeneous ribonucleoprotein and may contribute to malignant transformation in various epithelial tissues, including human colonic cells (21, 24 -26).…”
supporting
confidence: 91%
See 2 more Smart Citations
“…This finding is consistent with the reported decline in binding of galectin-3, -7, and -9 to more highly sulfated chondroitin, which was observed by frontal affinity chromatography (23). Coincident with reduced binding of galectin-3 to C4S, we have shown increases in nuclear galectin-3, which enabled transcriptional events mediated by AP-1, including increased expression of HIF-1␣ and versican, in human bronchial, colonic, and prostate cells (21,22). Galectin-3 interacts with heterogeneous ribonucleoprotein and may contribute to malignant transformation in various epithelial tissues, including human colonic cells (21, 24 -26).…”
supporting
confidence: 91%
“…Previously, experiments demonstrated that carrageenan exposure reduced ARSB activity (27) and that decline in ARSB led to transcriptional events that were attributable to the reduced association of galectin-3 with the more highly sulfated C4S present when ARSB activity was less (21,22). Wnt9A expression increased to 2.8 times the baseline in NCM460 cells and to 2.4 times the baseline in C57BL/6J mice following exposure to carrageenan, and exposure to the reactive oxygen species scavenger Tempol inhibited the increase in Wnt9A in the NCM460 cells (3).…”
Section: Expression Of Wnt9a Is Increased After Carrageenan or Arsb Smentioning
confidence: 99%
See 1 more Smart Citation
“…Extracellular and intracellular signals may be integrated through modulation of ARSB activity by oxygen and the associated changes in chondroitin 4-sulfation [15]. Subsequent variation in binding to more or less sulfated C4S can then regulate other cell processes, as shown by effects on galectin-3 leading to increased transcription of versican, HIF-1α, and Wnt9A in human epithelial cells and in the ARSB-deficient mouse [2,15,16]. The studies in this report address the impact of ARSB on BMP4/Wnt mediated CHST11 expression in intestinal epithelium and provide a new perspective on the interaction between degradation and synthesis of CS.…”
Section: 0 Introductionmentioning
confidence: 99%
“…NRX was immunoprecipitated from control and treated samples by the coated beads. Eluted protein was subjected to thiol:disulfide assay, and reduced NRX was detected by applying the methods previously used to detect total cellular thiol and sulfide content (Molecular Probes, Eugene, OR), in which cystamine, papain, and N α -benzoyl-L-arginine p-nitroanilide hydrochloride (L-BAPNA) were used (24)(25)(26). To measure the NRX thiol groups, cystamine was added, and cystamine underwent an exchange reaction with NRX, yielding 2-mercaptoethylamine (cysteamine), which then interacted with the disulfide bond of papain, yielding the active enzyme papain from its inactive S-S form.…”
Section: Immunoprecipitation Of Nrx and Detection Of Reduced Nrxmentioning
confidence: 99%